Emulsion stability of sugar beet pectin fractions obtained by isopropanol fractionation. (January 2018) - Karnik, Deepika; Wicker, Louise
Abstract: Protein rich (F1) and protein poor (F4) fractions of sugar beet pectin (SBP). Protein rich F1, protein poor F4, and control SBP were used to make oil-in-water emulsions with 0.5% or 1.5% SBP (F1_0.5, F1_1.5, F4_0.5, F4_1.5 or C_1.5) and 15% (medium chain triglyceride) MCT oil and emulsifying activity was determined. Changes in D[4, 3], light microscopy and rheological parameters during storage at 32 °C for 10 days indicated that SBP fraction and concentration influenced emulsion stability. Emulsions prepared with 0.5% fraction F4_0.5, with lower protein and surface hydrophobicity, had a D[4, 3] values less than 1 μm, which remained the same during storage. D[4, 3] values of emulsions, prepared with the 1.5% fraction F1_1.5 with higher protein and surface hydrophobicity, increased from 1.42 to 2.09 μm at 10 d. Emulsions prepared with unfractionated control SBP were intermediate in particle size. Emulsions prepared with F4_1.5 and F1_0.5 had higher D[4, 3] values of 3.45 and 4.18 μm after 10 d, respectively. There were no significant changes in viscosities of individual emulsions over 10 days. Emulsions were shear thinning or near Newtonian. Protein poor Fraction F4 with greater hydrophile/lipophile ratio formed more stable emulsions at 0.5%, but not at 1.5%, compared to protein rich Fraction F1 at 1.5%. Graphical abstract: Highlights: Emulsifying activity of Sugar beet pectin fractionated with isopropanol. Concentration of SBP fraction influenced emulsifying activity. Greater hydrophilic to hydrophobic ratio had greatest emulsifying activity.